Review on composition properties, functionalization of bio-oil and its rejuvenation behavior and mechanism on aged asphalt - Peilong Li; Lei Yue; Zhan Ding; Xiuming Jiang; Huifeng Li; Linyu An; Chenxi Tian (Journal of Road Engineering)
The objective of this paper is to comprehensively review the research progress of bio-oil properties and hot rejuvenation behavior and mechanism to aged asphalt. The preparation process, composition characteristics of bio-oils and their component correspondence with petroleum asphalt were compared. The diffusion and fusion effects of various bio-oils in aged asphalt were introduced. Bio-oil cannot be used as a direct alternative of petroleum asphalt, but it has the potential to effectively rejuvenate aged asphalt binders due to the component similarity with petroleum asphalt and good diffusion properties. For the asphalt rejuvenation, the functionalization treatment methods of bio-oil were discussed such as purification, composition modification and component conversion. The active groups and derivatives in bio-oil can be converted into the missing components of the aged binder through phenolate, grafting, polycondensation, resinifying, but the conversion process and mechanism are still unclear. From the perspectives of diffusion behavior, components regulation, dissolving asphaltene and micro-rejuvenation effect, the rejuvenation behavior and mechanism of bio-oil on aged asphalt were elaborated, and the effects of various types of bio-oil and aged asphalt on rejuvenation behavior were analyzed. The preparation process and dosage of bio-rejuvenator were summarized. The rejuvenation effects of bio-oil on aged asphalt were comprehensively investigated from the aspects of high and low temperature performances, rheological properties, microstructure and chemical composition of bio-rejuvenated asphalt binders. Finally, the limitations of bio-oil used as asphalt rejuvenators were discussed, and future research directions were prospected, which can provide reference and theoretical basis for the development of high-performance bio-oil rejuvenating agents and the engineering application of bio-oil to improve the properties of aged asphalt materials.